I-Media as post-nonclassical format of public communications - A.E. Bogoyavlensky (Ученые записки Казанского университета: Серия Гуманитарные науки)
Considering that the term “new media” has become outdated, the author argues on the possibility of introducing the concept of “I-Media”, which is understood as a phenomenon of the postnonclassical paradigm in development of the theoretical knowledge about digital communications, interpreted as independent media, I media, integrated media, Internet media, and information society media at the sub-branch, branch, inter-branch, trans-branch, and super-branch levels, respectively. The sub-branch level reflects the general idea of new media as uncontrolled powerful and structured means of communication. The branch level follows the formula “I am – I-M” and is able to reflect the author's view on the processes of media persuasiveness. The interbranch level rests upon the ideas of integrated communications in the paradigm of postnonclassical science. The transbranch level indicates possible uptake of I-Media as one of autopoetic systems. The super-branch level provides a basis for describing the common view of the above-mentioned layers. Thus, from the standpoint of civilizational development, the transformation of media can be embedded in the development of humans (Homo Sapiens – Homo Mediatus – Homo Internetus – Internet Sapiens), which means the gradual elimination of the process of evolution of the values of “Homo”. The author believes that the guidance of “synergy focus” will allow: firstly, to imagine a global media system (mediaevalists) residing in the phase of transition from globalization to glocalization, as dissipative structures; secondly, to reflect on the possibility of post-nonclassical transformation of the metaphor of McLuhan's “the medium is the message”; thirdly, to consider relevant, through still understudied, aspects of media theory in the context of the present stage of development of the scientific paradigm.